1998
DOI: 10.1108/02651339810236353
|View full text |Cite
|
Sign up to set email alerts
|

Explaining export development through psychic distance: enlightening or elusive?

Abstract: The concept of psychic distance has gained widespread theoretical recognition as a predictor of export behaviour. However, the empirical validation of the concept remains patchy and contradictory in terms of the results obtained. Consequently, this paper attempts to shed fresh light on the empirical usefulness of the psychic distance concept. First, a wider assessment base is offered through the development of two new US samples. Subsequently, the US findings are compared with previous empirical evidence from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 34 publications
1
110
0
3
Order By: Relevance
“…Axinn and Matthyssens (2002) identified psychic distance as an issue relating to the continued relevance of stage models of internationalization. Despite a belief that firms would be likely to expand into markets with high cultural proximity, Stöttinger and Schlegelmilch (1998) disagreed, suggesting that market globalization had outdated the concept of psychic distance. Loane and Bell (2006) identified that rapidly internationalizing SMEs increasingly perceived a global marketplace.…”
Section: Firm Age and Exportingmentioning
confidence: 99%
“…Axinn and Matthyssens (2002) identified psychic distance as an issue relating to the continued relevance of stage models of internationalization. Despite a belief that firms would be likely to expand into markets with high cultural proximity, Stöttinger and Schlegelmilch (1998) disagreed, suggesting that market globalization had outdated the concept of psychic distance. Loane and Bell (2006) identified that rapidly internationalizing SMEs increasingly perceived a global marketplace.…”
Section: Firm Age and Exportingmentioning
confidence: 99%
“…Stöttinger and Schlegelmilch (1998) performed an empirical investigation on the usefulness of the psychic distance concept on export development in US and compared the results with Japan, Germany, Finland and Austria. Wiedersheim-Paul et al (1978) developed a model that emphasizes on the relative importance of a business activities and "pre-export" behavior for the export start.…”
Section: Introductionmentioning
confidence: 99%
“…Also, factors such as foreign asset and foreign employee ratios of exports companies based on the company (Dörrenbacher, 2000) coincided with human and sales factors. On the other hand, in the process of internationalization, the physical proximity as well as the cultural proximity factor (Stöttinger and Schlegelmilch, 1998) was influenced by the country diversity (Zahra et al, 2000). Therefore, the necessity of establishing a system that adapts its employees to foreign cultures of operation, at least in terms of foreign language knowledge, as well as an analysis of exports companies based on the country culture could be considered within the human and country factor in this study.…”
Section: Discussionmentioning
confidence: 99%